2021
DOI: 10.1007/s10853-020-05711-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic tethered silver nanoparticles on reduced graphene oxide for alkaline oxygen reduction catalysis

Abstract: There is currently an enormous drive to move away from the use of Pt group metals in catalysis, particularly for fuel cells, because of their increasing rarity and cost. Simultaneously, there have been advances in the application of graphene supported nanoparticular catalysts. However, these Pt-free, graphene supported catalysts can be complex to produce, show poor catalytic activity and degrade quickly due to particle agglomeration or isolation. Herein, we report a one-pot synthesis of silver nanoparticles (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Tinker et al synthesized and compared EA and AP-based precursors in their study. [27] Both precursors could decompose into elemental Ag with similar particle size, but their Oxygen Reduction Reaction (ORR) activities showed that the onset potential of the AP precursor was higher than that of the EA precursor. It was reported that the relative pKa values of the respective alkanolamine might positively affect their binding abilities and influence the variation of onset potential from linker to linker.…”
Section: (2 Of 11)mentioning
confidence: 99%
“…Tinker et al synthesized and compared EA and AP-based precursors in their study. [27] Both precursors could decompose into elemental Ag with similar particle size, but their Oxygen Reduction Reaction (ORR) activities showed that the onset potential of the AP precursor was higher than that of the EA precursor. It was reported that the relative pKa values of the respective alkanolamine might positively affect their binding abilities and influence the variation of onset potential from linker to linker.…”
Section: (2 Of 11)mentioning
confidence: 99%
“…Both these applications, however, involve the synthesis of Ag NPs with a narrow size distribution which is challenging. 6,7 NP aggregation is a constant hindrance in both these applications which affects the functionality of the final device, while also reducing the shelf life of the inks/complexes. The deposition of NP inks for use in printed electronics also faces issues with printer clogging, high temperature sintering and the need for additives, all of which are detrimental to the final device.…”
Section: Introductionmentioning
confidence: 99%